45.7k views
1 vote
G(a)=-4a +4h(a)=-2a²-4find (g-h) (8)

1 Answer

2 votes

Given:


\begin{gathered} g(a)=-4a+4 \\ h(a)=-2a^2-4 \end{gathered}
(g-h)(8)\text{ is}

Firstly (g-h)(a) is:


\begin{gathered} g(a)=-4a+4 \\ h(a)=-2a^2-4 \\ (g-h)(a)=-4a+4-(-2a^2-4) \\ (g-h)(a)=-4a+4+2a^2+4 \\ (g-h)(a)=2a^2-4a+8 \end{gathered}

At a=8.


\begin{gathered} (g-h)(a)=2a^2-4a+8 \\ (g-h)(8)=2(8)^2-4(8)+8 \\ (g-h)(8)=(2*64)-32+8_{} \\ (g-h)(8)=128-32+8 \\ (g-h)(8)=104 \end{gathered}

User Neeraj Singh
by
5.8k points